Antimicrobial and Enzymatic Profiling of Halophilic and Halotolerant Bacteria from a Hypersaline Lake 'The Great Sebkha of Oran, Northwestern Algeria'. Issue 9 (1st September 2022) - Saibi, Amina Nour Elhouda; Nas, Fatima; Arab, Mounia; Aissaoui, Nadia; Boukeroui, Yasmina; Klouche-Khelil, Nihel
Abstract: Extreme ecosystems such as hypersaline habitats are promising source of bacteria able to produce potent natural molecules. Halophilic and halotolerant bacteria associated with an unexplored dry salt lake in Algeria have been investigated. A total of 17 isolates were phenotypically characterized. Optima temperature, pH, and salt concentration for growth have been determined. Bacteria strains have been identified based on the 16S rRNA gene sequencing. Enzymes production and antimicrobial activity against bacteria and fungi strains have been investigated. The results showed that isolates were assigned to three phylotypes, within eight isolates belonging to the genus Virgibacillus, eight isolates to Bacillus, and the genus Halomonas with one representative isolate. All phylotypes were able to thrive on large scales of salt, temperature and pH. In addition, the screening of extracellular enzymes showed that all the isolates were able to produce at least two enzymes. The gelatinase, and caseinase activities were the most produced. The screening of antimicrobial compounds production revealed that these strains exhibited significant activity against Gram-positive, Candida albicans, Fusarium, and Penicillium species. Finally, this biotechnological profiling and the PCA analysis have been shown that LMB3038, LMB3095, and LMB3082 were the most performant strains and present a promising source of important molecules.